DETERMINAN KUALITAS AUDIT PEMERINTAH DI INDONESIA: PERANAN TIME BUDGET PRESSURE SEBAGAI VARIABEL MODERASI - Theresia Prima Risanti (2021)
In producing reliable audit quality, it also requires the quality of the auditors themselves. The Financial and Development Planning Agency (BPKP) is a state institution that is part of the Government Internal Supervisory Apparatus (APIP). In 2013, BPKP admitted corruption as quoted on detik.com. It can be assumed that there are indications that the audit results conducted by BPKP have been influenced by the interests of certain parties. This study aims to determine the effect of auditor skepticism, understanding of information systems, auditor education, and audit motivation on audit quality and also to determine the effect of time budget pressure in moderating the influence of audit motivation on audit quality. This research was conducted at BPKP DKI Jakarta using a questionnaire instrument. The research data were processed using SEM-PLS. The results of this study found that auditor skepticism has a significant effect on audit quality. Meanwhile, understanding of information systems, auditor education, and audit motivation has no effect on audit quality. Time budget pressure also has no influence to moderate the effect of audit motivation on audit quality.